Legal Politics of Restitution for Victims of Malguardian Arrests Based on The Principle of Justice - Hidayati, Hidayati; Wijanarko, Adityo; Al Rais, Azis; Pandopotan, Victor Hisar (Yayasan Meira Visi Persada, 2026)
In general, law enforcement by law enforcement officers is a process of taking legal actions and efforts to uphold and maintain the functioning of legal norms as guidelines for behavior in legal relations and events within society, the nation, and the state. Considering the scope of law enforcement, it should include the enforcement of justice itself. Legal actions and efforts to uphold and maintain the functioning of legal norms as guidelines for behavior in legal relations and events indicated as violations of the law by individuals or suspects are philosophically implemented by adhering to the principle of the presumption of innocence. In the legal process for suspects and defendants in connection with a criminal act, the alleged suspect has the right to legal protection and respect for their human rights, as regulated by Law Number 8 of 1981 concerning the Criminal Procedure Code. The question is: How does the legal policy of restitution for victims of wrongful arrest align with the principle of justice? Based on this issue, the provisions of the Criminal Procedure Code stipulate that in a legal process involving a criminal act, law enforcement during the investigation process does not have the authority to act arbitrarily, let alone ignore applicable laws and regulations. The existence of a verdict of not guilty or acquittal against a suspect or defendant decided by a judicial institution, then the legal implications are concerning or related to the rights of the suspect or defendant that must be protected by the State as also regulated in Article 95 of the Criminal Procedure Code, that in principle the suspect or defendant has the right to sue for compensation.